2009
DOI: 10.1371/journal.pone.0006841
|View full text |Cite
|
Sign up to set email alerts
|

Music Attenuates Excessive Visual Guidance of Skilled Reaching in Advanced but Not Mild Parkinson's Disease

Abstract: Parkinson's disease (PD) results in movement and sensory impairments that can be reduced by familiar music. At present, it is unclear whether the beneficial effects of music are limited to lessening the bradykinesia of whole body movement or whether beneficial effects also extend to skilled movements of PD subjects. This question was addressed in the present study in which control and PD subjects were given a skilled reaching task that was performed with and without accompanying preferred musical pieces. Eye m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…The skilled reaching task, in which a subject reaches for a small food item, grasps the food item with the fingers, and then transports the food item to the mouth for eating (Whishaw et al, ), can be used experimentally to describe and quantify hand use deficits. This task can be used to examine forelimb and postural impairments in human conditions such as Parkinson's disease (Sacrey et al, ), Huntington's disease (Klein et al, ), and stroke (Foroud and Whishaw, ), and can also be used to model Parkinson's disease (Whishaw et al, ; Montoya et al, ; Whishaw and Pellis, ; Miklyaeva et al, ), Huntington's disease (Fricker‐Gates et al, ; Whishaw et al, ), and stroke (Gharbawie et al, ; Alaverdashvili and Whishaw, ) in rodents (for further references, see the staircase skilled reaching database at http://www.cf.ac.uk/biosi/staffinfo/dunnett/stairref.html).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The skilled reaching task, in which a subject reaches for a small food item, grasps the food item with the fingers, and then transports the food item to the mouth for eating (Whishaw et al, ), can be used experimentally to describe and quantify hand use deficits. This task can be used to examine forelimb and postural impairments in human conditions such as Parkinson's disease (Sacrey et al, ), Huntington's disease (Klein et al, ), and stroke (Foroud and Whishaw, ), and can also be used to model Parkinson's disease (Whishaw et al, ; Montoya et al, ; Whishaw and Pellis, ; Miklyaeva et al, ), Huntington's disease (Fricker‐Gates et al, ; Whishaw et al, ), and stroke (Gharbawie et al, ; Alaverdashvili and Whishaw, ) in rodents (for further references, see the staircase skilled reaching database at http://www.cf.ac.uk/biosi/staffinfo/dunnett/stairref.html).…”
Section: Commentarymentioning
confidence: 99%
“…Current Protocols in Neuroscience Supplement 58 task can be used to examine forelimb and postural impairments in human conditions such as Parkinson's disease (Sacrey et al, 2009b), Huntington's disease (Klein et al, 2011), and stroke (Foroud and Whishaw, 2006), and can also be used to model Parkinson's disease (Whishaw et al, 1986;Montoya et al, 1990;Whishaw and Pellis, 1990;Miklyaeva et al, 1994), Huntington's disease (Fricker-Gates et al, 2003;Whishaw et al, 2007), and stroke (Gharbawie et al, 2008;Alaverdashvili and Whishaw, 2010) in rodents (for further references, see the staircase skilled reaching database at http: //www. cf.ac.uk/biosi/staffinfo/dunnett/stairpubdate.…”
Section: 2811mentioning
confidence: 99%
“…upper-limb tasks and turns-in-place) these related outcomes were oppositely impaired (i.e. reduced saccade velocity and amplitude and increased frequency) (Anastasopoulos et al, 2011, Desmurget et al, 2004, Lohnes and Earhart, 2011, Sacrey et al, 2009, Sacrey et al, 2011, Ventre-Dominey et al, 2002, Ventre-Dominey et al, 2001, illustrating a selective effect of impairment.…”
Section: Interpretation Of Outcomesmentioning
confidence: 95%
“…FOG), cognitive and visual deficits was reported in four of the reviewed studies (Galna et al, 2012, Lee et al, 2012, Uc et al, 2006, Lohnes and Earhart, 2011, however the majority did not report or control for cognition or basic visual function (visual acuity and contrast sensitivity). Many studies either excluded or did not assess cognition (Desmurget et al, 2004, Lohnes and Earhart, 2011, Marx et al, 2012, Sacrey et al, 2009, Vitório et al, 2012, Vitorio et al, 2013. Two studies (Galna et al, 2012, Uc et al, 2006 assessed basic visual function and several studies did not include participants who wore glasses (Anastasopoulos et al, 2011, Sacrey et al, 2009, Sacrey et al, 2011.…”
Section: Interpretation Of Outcomesmentioning
confidence: 99%
“…Our findings also suggest that if vision or a visual memory of target location is available, it can be used to compensate for proprioceptive impairments. Other studies have also suggested that PD patients rely excessively on visual information to compensate for impairments in proprioceptive guidance (Zia et al 2000;Seiss et al 2003;Sacrey et al 2009). …”
Section: Selective Deficits In Proprioceptively Based Movement Guidanmentioning
confidence: 99%